1983
DOI: 10.1002/j.1460-2075.1983.tb01606.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in translatable mRNAs for the cerebral enolase isozymes alphaalpha and gammagamma.

Abstract: Using the rabbit reticulocyte cell-free translation system we have estimated during ontogenesis the proportions of in vitro translatable a and oy brain enolase mRNAs, which are two minor mRNA species. No polypeptide precursor to these enzyme subunits appears to be synthesized during translation in vitro. During brain development, the changes in translatable a and 'y mRNA content seem to parallel those of the corresponding antigens. The proportion of each of the enolase mRNAs is highest in adult mouse brain. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
2
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
3
2
0
Order By: Relevance
“…The largest increase occurs between postnatal weeks 1 and 2, after which a moderate increase gives rise to adult levels. These results are roughly consistent with measurements of NSE mRNA by its ability to program in vitro protein synthesis [Zeitoun et al, 1983;Yoshida et al, 19831, although in rats we observe a lesser increase in phase 2 than do Zeitoun et al, who studied mice.…”
Section: Comparison With Other Enolase Lsozymessupporting
confidence: 92%
“…The largest increase occurs between postnatal weeks 1 and 2, after which a moderate increase gives rise to adult levels. These results are roughly consistent with measurements of NSE mRNA by its ability to program in vitro protein synthesis [Zeitoun et al, 1983;Yoshida et al, 19831, although in rats we observe a lesser increase in phase 2 than do Zeitoun et al, who studied mice.…”
Section: Comparison With Other Enolase Lsozymessupporting
confidence: 92%
“…We identified seven proteins up-regulated in the adult brain when compared to neonatal mice, including g enolase, annexin V, glutamine synthetase, two isoforms of creatine kinase B chain, triosephosphate dehydrogenase, and malate dehydrogenase. The proportion of each of the enolase mRNAs was found to be highest in adult mouse brain [37]. Consistent with this mRNA study, we found a significant increase of g enolase protein in adult brain, whereas a enolase increased only marginally according to our statistical test.…”
supporting
confidence: 90%
“…We have also demonstrated that switching of aa enolase to /3p during development of chicken skeletal muscle was regulated at the transcriptional level (Tanaka et al, 19856). A similar mechanism was also observed in the brain of rat (Yoshida et al, 1983) or mouse (Zeitoun et al, 1983).…”
Section: Discussionsupporting
confidence: 74%
“…It has been reported that a and y enolase precursors can be synthesized in a rabbit reticulocyte cell-free translation system using poly(A)+ RNA from the brain of rat (Walker and Zomzely-Neurath, 1980;Sakimura et al, 1982;Yoshida et al, 1983) or mouse (Zeitoun et al, 1983). In the present study, a and y prepolypeptides were also synthesized in the translation system programmed with polysomal-poly(A)+ RNA prepared from 4-day-old chicken brain.…”
Section: Discussionmentioning
confidence: 49%